The Flow of Cultural Transmission Through Storytelling to the Generation Z in Vietnam - Thu, Nguyen Hoang Anh; Khang, Nguyen Tan (English Department, Faculty of Humanities, Andalas University, 2024)
Children growing up in Vietnam have mostly heard stories from their family members. At that time, the stories contain cultural knowledge that is preserved and passed down from generation to generation. This study examines the experiences of young people belonging to the Gen Z generation in Vietnam, in the case of students of the University of Social Sciences and Humanities, Viet Nam National University Ho Chi Minh City with storytelling and exploring the characteristics of cultural transmission from the previous generation to the following generation through the form of storytelling. To explore these issues, the authors used a mixed research design combining qualitative and quantitative research. The results from the quantitative study show data on the students’ access to storytelling from childhood to the present, while the data from the qualitative study exploit personal experiences to cross-check with the quantitative data. The results of the study show that close relatives such as fathers, mothers, grandparents, teachers or acquaintances are the ones who often transmit culture through the form of storytelling from the students’ childhood. The cultural transmission form contained in the stories is in the form of folklore, literary works, religious stories, stories related to personal experiences and some other types. Storytelling plays the role of knowledge products for the purpose of cultural transmission through the generations. Through that, Gen Z students are provided with spiritual motivation for their own lives. And from there, they also become the ones who continue to transmit culture to the next generation.